2012
DOI: 10.1007/s13238-012-2918-4
|View full text |Cite
|
Sign up to set email alerts
|

Human induced pluripotent stem cells derived hepatocytes: rising promise for disease modeling, drug development and cell therapy

Abstract: Recent advances in the study of human hepatocytes derived from induced pluripotent stem cells (iPSC) represent new promises for liver disease study and drug discovery. Human hepatocytes or hepatocyte-like cells differentiated from iPSC recapitulate many functional properties of primary human hepatocytes and have been demonstrated as a powerful and efficient tool to model human liver metabolic diseases and facilitate drug development process. In this review, we summarize the recent progress in this field and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 28 publications
1
35
0
1
Order By: Relevance
“…Similarly to many other reports of iPSC-based disease modeling, efficient differentiation of patient-specific iPSC into disease-affected cell types represents a critical challenge to the success of the study. Among many established differentiation protocols, efficient differentiation of human pluripotent stem cells into functional hepatocytes is technically challenging, in spite of its tremendous application potential (Yi et al, 2012). In line with many other reports, we observed that the HLC differentiated from patient iPSC resemble many important features to PHH and exhibit functionality in vitro, however, they do not fully match the maturation level of PHH.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly to many other reports of iPSC-based disease modeling, efficient differentiation of patient-specific iPSC into disease-affected cell types represents a critical challenge to the success of the study. Among many established differentiation protocols, efficient differentiation of human pluripotent stem cells into functional hepatocytes is technically challenging, in spite of its tremendous application potential (Yi et al, 2012). In line with many other reports, we observed that the HLC differentiated from patient iPSC resemble many important features to PHH and exhibit functionality in vitro, however, they do not fully match the maturation level of PHH.…”
Section: Discussionsupporting
confidence: 79%
“…One of the main advantages of using iPSCs is that they allow the really impact of genetics on cell responses to drugs to be studied. Generation of iPSCs from clinically identified donors that exhibit different drug sensitivities and metabolizing enzymes would increase the predictivity of toxicity assays (Anson et al 2011;Kia et al 2013;Medine et al 2013;Yi et al 2012) (Fig. 2).…”
Section: The Use Of Ipscs-derived Hlcs For Hepatotoxicity Assessmentmentioning
confidence: 99%
“…Perhaps in the future, hepatocytes from iPSCs generated from specific patients afflicted with idiosyncratic hepatotoxicity may provide insights into the role of genetic diversity in DILI (Takayama et al 2014;Mann 2015). Generating panels of human iPSC-derived hepatocytes from individuals with different CYP polymorphisms would also be extremely valuable for drug metabolism, drug-drug interactions and more accurate toxicity predictions in humans of new drugs in preclinical stages to enable more successful clinical trials, which would shorten the timeline and reduce costs (Anson et al 2011;Yi et al 2012;Medine et al 2013;Holmgren et al 2014;Takayama et al 2014;Davidson et al 2015). iPSCs also offer the opportunity to generate liver cells in different maturation stages, as well as the potential to give rise to all the composite cells of the adult liver (Baxter et al 2010;Medine et al 2013).…”
Section: Future Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it was urgent to develop a high-fidelity human hepatocytes model such as hiPSCs. These cells offer promising opportunities for highthroughput drug screening in a cost-effective manner, with enhanced reproducibility and decreased risks of failure during preclinical stages [41]. It is important to note that hiPSCs-derived hepatocytes enable the establishment of a wide spectrum of readily available hepatocyte lines, which represent the potential genetic and epigenetic variations of a human population.…”
Section: Drug Developmentmentioning
confidence: 99%